Development and validation of a quantitative measure for parent empowerment via transformative learning - To, Siu-ming; Yang, Lei; Dong, Lei; Yan, Ming-wai; So, Yuk-yan; Chung, Mee-yee (Frontiers in Psychology, 2022)
Although current literature demonstrates how parents benefit from parent empowerment programs, the development of a quantitative measure of parent empowerment has garnered limited attention in parenting research. The goal of this research was therefore to develop and validate a quantitative measure for the assessment of practitioners’ attitudes and competence in parent empowerment. In the process of item generation, the qualitative findings derived from four studies in relation to the perceived outcomes and experiences in parent empowerment were synthesized in the first stage. In the second stage, a list of narratives that articulated different themes of parent empowerment were generated, which resulted in an item pool containing 28 items. In the third stage, the research team converted the 28 items into a survey instrument. In the fourth stage, a first scale validation study was conducted to explore the factor structure of the initial 28-item questionnaire. The exploratory factor analysis on the first sample of 366 practitioners yielded a twofold factor structure with 17 items, including practitioners’ attitudes in parent empowerment and practitioners’ competence in parent empowerment. In the final stage, a second scale validation study was undertaken to verify the fit of the twofold factor structure. A confirmatory factor analysis on the second sample of 170 practitioners demonstrated a good model fit. The results of reliability tests for the whole scale and two subscales also indicate satisfactory internal consistency. The Parent Empowerment via Transformative Learning Questionnaire (PETLQ) was thus developed and confirmed as a scale with sufficient factorial validity and internal consistency to be used for assessing parenting practitioners’ attitudes and competence in parent empowerment and for evaluating the effectiveness of parent empowerment programs.